The Psychology of Women's Health: Progress and Challenges in Research and Application. 1995
DOI: 10.1037/10178-006
|View full text |Cite
|
Sign up to set email alerts
|

Menarche, menstruation, and menopause: Psychosocial research and future directions.

Abstract: he biological aspects of women's menstrual life-of menarche, men-T struation, and menopause-are the same in different cultures, but the contexts differ and contribute to a diversity of personal experience. In Western culture, menarche is given little formal recognition; there are no ceremonies, celebratory rituals, or symbols. It is considered a major biological event, but its psychological significance is largely ignored. In contrast, considerable psychological significance is attributed to menstruation and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 92 publications
0
13
0
Order By: Relevance
“…Women who are current smokers or ex-smokers have a higher risk of menstrual symptoms and miscarriage than women who have never smoked cigarettes, after controlling for potential confounders. 27 2. These risks increase both with the number of cigarettes smoked and with the age of starting to smoke.…”
Section: Mishra Dobson and Schofieldmentioning
confidence: 99%
“…Women who are current smokers or ex-smokers have a higher risk of menstrual symptoms and miscarriage than women who have never smoked cigarettes, after controlling for potential confounders. 27 2. These risks increase both with the number of cigarettes smoked and with the age of starting to smoke.…”
Section: Mishra Dobson and Schofieldmentioning
confidence: 99%
“…Women's depression has been variously associated with marital status (Harlow, Cohen, Otto, Spiegelman, & Cramer, 1999), education level (Malacara et al, 2002), health status (Heidrich, 1994;Woods & Mitchell, 1997), menopause stage (Bromberger et al, 2001), and hormone replacement therapy (HRT) use (Li et al, 2002). Gallant and Derry (1995) generalized previous studies and claimed that observed increases in depression are associated with psychosocial factors such as previous history of depression and other health problems rather than with menopause status.…”
Section: Potential Factors Related To Menopause Depressionmentioning
confidence: 94%
“…Explorations of women's physical health are increasingly sensitive to stereotypes of women's physical maladies as psychologically based (Goudsmit, 1994); of andocentric expectations about the onset, symptoms, and treatment of chronic illnesses (e.g., Shumaker & Smith, 1995); and of syndromes that pathologize common female experiences including menstruation (Caplan, 1995; Gallant & Derry, 1995), childbirth (Stanton & Danoff-Burg, 1995), abortion (Adler, David, Major, Roth, Russo, & Wyatt, 1990), and miscarriage (Madden, 1994). When gender is regarded more fully as a marker, not an explanatory cause of differences in women's and men's mental and physical health, researchers can begin to explore the impact of job-role quality and family experiences on health outcomes (Barnett, 1997).…”
Section: Generalizing the Approachmentioning
confidence: 99%